The Effects of Long Soaking Seeds and Phosphate Fertilizer on Growth and Yield of Peanuts (Arachis hypogaea) - R. Iin Siti Aminah; Ahmad Sofian; Rosmiah Rosmiah; Neni Marlina; Maria Lusia; Kharisma Oktavia (Universitas Muhammadiyah Palembang, 2023)
Peanuts are a potential agricultural commodity after soybeans. Peanut production increased after 2017 but in 2018 it decreased. This occurs due to several obstacles, especially poor soil conditions, especially in several areas in South Sumatra. One effort to increase production is done by fertilizing according to the conditions and correct seed management. This research was carried out to determine the length of soaking of seeds in liquid biological fertilizer and giving different doses of phosphate fertilizer to peanuts, which was carried out from July to October 2020 in Pulau Semambu Ogan Ilir Village, South Sumatra. The experiment was carried out using a factorial randomized block design with 2 treatment factors, namely the length of immersion (0. 15 and 30 minutes) and the administration of a dose of phosphate fertilizer (50,75,100 and 125 kg / ha). The treatment of soaking seeds for 30 minutes gave the best results on the variables of the number of pods planted, the number of empty pods planted, the weight of the planted pods, the weight of the pods per plot, and the weight of 100 seeds. Treatment of phosphate fertilizer dose of 100 kg / ha gave the best results on the variables of number of pods planted, weight of planted pods, weight of pods per plot and weight of 100 seeds. The interaction between the duration of soaking the seeds for 30 minutes with a dose of phosphate fertilizer of 100 kg / ha by tabulation gave the highest yield of 1.28 kg / plot or equivalent to 3.41 tons / ha.